Sining Kambayoka’s Usa Ka Damgo: Transplanting Shakespeare into Lanao (Asia Pacific Journal of Social Innovation, 2022)
This paper explores and lays bare how the study of Shakespeare’s A Midsummer Night’s Dream in its translation or adaptation brings artistic and theatrical invigoration and opens up possibilities of dialogues between the local and western cultures. Zeroing-in on Sining Kambayoka’s Usa ka Damgo, this study also discusses how the translated work exemplifies this opportunity for creative invigoration in theater and the potential for building an avenue to connect vastly distant cultures as it resituates A Midsummer Night’s Dream, a cultural product from the west, into not one but two Philippine cultures – Cebuano and Maranao.This paper’s purpose is anchored on this opportunity and potential: to investigate Sining Kambayoka’s practice of translating and adapting not only on the linguistic level of translation, but also on the often neglected yet more crucial aspect of translation – cultural mediation. The paper concentrates on the cultural transformation that occurs in the transfer between the source and the target text. Particularly, the paper examines how culture is negotiated in the translation process to suit the cultural context, and the target audience of the performance. By understanding how a narrative set in a different period and distant place converses with the local Maranao setting, it is then possible to assess this particular translation of A Midsummer Night’s Dream.The study reveals that the strategies employed by the translators may be grouped into two approaches: selective suppression and re-creative translation. Omission, reduction and implicitation are strategies that selectively suppress the source text by stripping the source text with elements that are no longer necessary in the target text, while expansion, amplification and adaptation are strategies that re-create the source text by means of adding cultural nuances that would lead to the re-location of the translated play. Both approaches aim at domesticating the foreign text such that the play becomes re-situated in the Lanao context.